Do not ignore multiple capillary malformations in a child - Calvão,Joana (2022)
Abstract Capillary malformation-arteriovenous malformation syndrome (CM-AVM) is a rare autosomal dominant disorder caused by heterozygous mutations in RASA1 and EPHB4 that associates multifocal capillary malformations (CMs) with an increased risk for fast-flow vascular malformations (FFVMs) which can cause life-threatening complications. We report the case of a 6-year-old girl with lip telangiectasia as well as multiple (>10) erythematous to brownish irregular macules and patches on the face, neck, trunk, and superior extremities from the age of 18 months with no local or systemic complaints. Several family members had similar lesions. Genetic testing revealed a heterozygous mutation in the EPHB4 gene, confirming the diagnosis of CM-AVM type 2. EPHB4 gene mutation was also present in her father and brother. No associated arteriovenous malformations (AVMs) were found after a thorough evaluation by cardiology and neurology, neither in the patient nor in the closest relatives. The present case is a characteristic presentation of CM-AVM type 2 syndrome, with gradually appearance of multifocal CMs, lip telangiectasias, and a positive family history, without associated extracutaneous FFVMs. An increasing number of atypical CMs on the skin may be the only sign of CM-AVM and should alert the clinician to further investigate the presence of AVMs which can be life-threatening.